2020
DOI: 10.3390/su12051737
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Urban Form on Thermal Environment Near the Surface Region at Pedestrian Height: A Case Study Based on High-Density Built-Up Areas of Nanjing City in China

Abstract: The continuous worsening of urban thermal environments poses a severe threat to human health and is among the main problems associated with urban climate change and sustainable development. This issue is particularly severe in high-density built-up areas. Existing studies on the thermal environments (temperature data extracted from satellite remote sensing images) are mainly focused on urban canopy areas (airspace below the average height of trees or buildings) rather than the near surface region (at pedestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In the current study, the HF increased by 41.7, which reduced the average air temperature by 0.92 • C in the block. Yang et al showed that there is no direct correlationship between the air temperature and BD [42], which is similar to the results presented in the current paper. In addition, in a study of Hong Kong City, Cheung et al showed that the air temperature can be increased by 0.849 • C [54] by increasing SVF from 0 to 1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the HF increased by 41.7, which reduced the average air temperature by 0.92 • C in the block. Yang et al showed that there is no direct correlationship between the air temperature and BD [42], which is similar to the results presented in the current paper. In addition, in a study of Hong Kong City, Cheung et al showed that the air temperature can be increased by 0.849 • C [54] by increasing SVF from 0 to 1.…”
Section: Discussionsupporting
confidence: 92%
“…The thermal environment and wind environment of six typical residential blocks in summer and winter solstice were simulated, and the air temperature and wind speed ratio of 6 monitoring points at the 1.5 m pedestrian level of each plot were analyzed during the period of 8:00-18:00. Combining the research scheme of Nanjing Xinjiekou and the investigation of Xi'an block morphology, we carried out the simulation study of idealized parameters as discussed in Section 2.3 [6,42]. BD refers to the proportion (%) of the total base area of buildings and the occupied land area within a certain range.…”
Section: Simulation Software and Parameter Settingsmentioning
confidence: 99%
“…When the ratio of increasing green area was fixed at 60%, there was a temperature reduction effect of at least −0.44 • C, up to −2.0 • C, depending on the installation rate of the permeable pavement. The last prior research identifies the effect of urban form and specific building functions on the thermal environment [12]. This study suggests that the optimal size, height, and layout of buildings were presented in different ways.…”
Section: Literature Reviewmentioning
confidence: 91%
“…The adaptation of urban areas to climate change is most challenging in compact areas, where changes to the urban form (e.g., street orientation, built density, average heights, built heritage, infrastructure) are difficult, at least compared to newly built areas [3]. While it is known that the urban form directly impacts urban microclimates [48], it is not likely that an entire block or a building listed as heritage will be demolished to improve, say, wind flow in an outdoor space. It follows that newly built forms are just the tip of the iceberg and that a more sustainable built environment calls for action upon existing buildings and infrastructures (and spaces) [49].…”
Section: Convivial Greenstreets Occur Mainly Where Climate-responsivementioning
confidence: 99%